2023
DOI: 10.1186/s13075-023-03074-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the immune-related biomarkers in Behcet’s disease by plasma proteomic analysis

Abstract: Background This study aimed to investigate the expression profile of immune response-related proteins of Behcet’s disease (BD) patients and identify potential biomarkers for this disease. Methods Plasma was collected from BD patients and healthy controls (HC). Immune response-related proteins were measured using the Olink Immune Response Panel. Differentially expressed proteins (DEPs) were used to construct prediction models via five machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Although disease manifestations were not statistically different between the two clusters, the results might be prone to type II error due to a small sample size. The cluster with male predominance, younger age and a shorter disease duration tended to have more frequent oral ulcers, genital ulcers, skin lesions, a higher disease activity, and less arthritis [30 ▪▪ ]. Among a number of proteins with differential expression in patients with and without uveitis, plexin A4, a neuropilin-binding protein and a semaphorin receptor implicated in the regulation of axonogenesis, was the most prominent and the difference was even more marked in the validation cohort [30 ▪▪ ].…”
Section: Pathogenetic Implications Of Clinical Clustering In Behçet's...mentioning
confidence: 95%
See 2 more Smart Citations
“…Although disease manifestations were not statistically different between the two clusters, the results might be prone to type II error due to a small sample size. The cluster with male predominance, younger age and a shorter disease duration tended to have more frequent oral ulcers, genital ulcers, skin lesions, a higher disease activity, and less arthritis [30 ▪▪ ]. Among a number of proteins with differential expression in patients with and without uveitis, plexin A4, a neuropilin-binding protein and a semaphorin receptor implicated in the regulation of axonogenesis, was the most prominent and the difference was even more marked in the validation cohort [30 ▪▪ ].…”
Section: Pathogenetic Implications Of Clinical Clustering In Behçet's...mentioning
confidence: 95%
“…The cluster with male predominance, younger age and a shorter disease duration tended to have more frequent oral ulcers, genital ulcers, skin lesions, a higher disease activity, and less arthritis [30 ▪▪ ]. Among a number of proteins with differential expression in patients with and without uveitis, plexin A4, a neuropilin-binding protein and a semaphorin receptor implicated in the regulation of axonogenesis, was the most prominent and the difference was even more marked in the validation cohort [30 ▪▪ ]. In the other study [31 ▪▪ ], researchers identified 220 out of 759 plasma proteins differentially expressed in 98 patients with Behçet's syndrome compared to 31 healthy controls.…”
Section: Pathogenetic Implications Of Clinical Clustering In Behçet's...mentioning
confidence: 97%
See 1 more Smart Citation
“…Microarray-based gene expression profiling has emerged as a prominent tool in biomedical research, enabling the identification of potential biomarkers. Studies have identified candidate biomarkers for both BD and VTE, including IL10, FCRL3, MASP1, NF2, FAM3B, and MGMT for BD 11 , and ISG15 , RPS15A , MRPL13 , ICT1 , MRPL15 , and RPLP0 for VTE 12 . Additionally, research suggests that circulating microRNAs (miR-20a-3p, miR-134, miR-522-3p, and miR-874) may regulate genes encoding exosome components ( TLN1 , LAMTOR3 , STX7 , and IMPA1 ), potentially influencing exosome involvement in VTE pathophysiology 13 .…”
Section: Introductionmentioning
confidence: 99%